KEDUDUKAN AKTA HIBAH DALAM SENGKETA KEPEMILIKAN HAK ATAS TANAH - Putri Wardhani (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTGrant is a one-sided agreement whichis the parties who are still alive, freelyand irrevocable, give or dissectingan object for the purpose of therecipient's receiving the comforter. Aa common problem in society is thattransitions land of rights through thegrants. This is could happen whensomeone wrong. The wrong partiessaid that they felt like had the grantor the parties who inherited thegrant. The solution should beestablished by viewing the form ofthe grant performed using anauthentic deed as prescribed inarticle 1682 of civil law. The generalthe authority is given to make the seed ofthe grant by the law is the land deed.The issue raised in this writing wasentitled.